2020
DOI: 10.32678/loquen.v13i2.3555
|View full text |Cite
|
Sign up to set email alerts
|

How E-Learning Deals with Higher Education during the Pandemic in Indonesia

Abstract: The purpose of this study is to investigate the obstacles of e-learning, especially for students, and to find out students' perception in facing e-learning during coronavirus disease pandemic (covid-19). The rapid spread of coronavirus urges universities on a world-wide scale to do e-learning, including universities in Indonesia. This study uses online interviews and questionnaires to obtain the data, and descriptive qualitative method is used to analyse the data. The respondents in this study are 126 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Infrastructure whose existence is not used for the teaching and learning process, but it directly supports the implementation of online learning, namely the home of each student, because the implementation of online learning is carried out learning from home. The availability and adequacy of facilities are one of the requirements to support the success of online learning or e-learning (Oladele & Modebelu, 2021); (Nugroho, 2020); (Silvana et al, 2021).…”
Section: Table 8 Correlation Test Resultsmentioning
confidence: 99%
“…Infrastructure whose existence is not used for the teaching and learning process, but it directly supports the implementation of online learning, namely the home of each student, because the implementation of online learning is carried out learning from home. The availability and adequacy of facilities are one of the requirements to support the success of online learning or e-learning (Oladele & Modebelu, 2021); (Nugroho, 2020); (Silvana et al, 2021).…”
Section: Table 8 Correlation Test Resultsmentioning
confidence: 99%
“…Furthermore, Altunay (2019) stated that EFL students met a lack of high-tech resources as well as technical issues while being satisfied with online education due to its flexibility. Because most students lack technology skills, Nugroho (2020) found that converting the entire learning process to online classrooms is not successful. The findings of other studies revealed that students had difficulty with technology (Islam et al, 2015;Atmojo & Nugroho, 2020;Jhon et al, 2020;Alodwan, 2021).…”
Section: Technical Challengesmentioning
confidence: 99%
“…In Indonesia, few studies have been carried out highlighting students' perceptions of the effectiveness of online classrooms. Nugroho (2020) focused on finding out students' perceptions in facing e-learning during COVID-19, resulting that e-learning was quite helpful even though most students faced problems such as internet credit and lack of technological knowledge.…”
Section: Introductionmentioning
confidence: 99%